Carbon nanotubes application for lithium-ion battery anodes - Mhlanga, Nqobile (University of the Witwatersrand, Johannesburg, 2024)
The most commonly used anode material for lithium-ion batteries (LIBs) is graphite, however it has some shortcomings such as having a low reversible capacity and low diffusion rate which produce low-power density batteries. Thus, the purpose of this study was to examine the application of carbon nanotubes (CNTs) as an alternative LIB anode material. A bimetallic iron-cobalt catalyst supported on calcium carbonate (Fe-Co/CaCO3) was used for the synthesis of CNTs and it was prepared using the wet impregnation method. X-ray diffraction (XRD) analysis of the catalyst showed that it was highly crystalline. The specific surface area (SSA) which was determined using Brunauer-Emmett-Teller (BET) was found to be 11.3 m2/g. CNTs were prepared using the chemical vapour deposition (CVD) method at various test parameters i.e. temperature (650°C,700°C,750°C and 800°C), hydrocarbon flow rate (90 mL/min and 120 mL/min) and carbon source (acetylene and ethylene). High-resolution transmission electron microscopy (HRTEM) results for samples synthesised at 650°C and 700°C using acetylene at a flow rate of 90 mL/min (650°C-A90 and 700°C-A90) showed that CNTs which were multiwalled carbon nanotubes (MWCNTs) in nature were produced. The formation of what appeared to be non-tubular carbon and carbon nanofibers was observed when the synthesis temperature was increased from 700°C to 800°C. The average outer diameter (OD) of the tubes ranged from 20 to 89 nm. At a higher acetylene flowrate (120 mL/min), the quality of CNTs seemed to deteriorate for synthesis temperatures above 650°C. The formation of non-tubular carbon-like nanofibers was observed at synthesis temperatures above 650°C. The average OD of the tubes ranged from 22 to 81 nm. XRD analysis of all samples synthesised using acetylene showed a similar pattern with the most intense peak being that of carbon and minor peaks being of iron. The samples also contained some broad peaks which suggested that the samples contained amorphous carbon. The calculated crystallite size ranged from 3.4 to 6.4 nm for samples synthesised using acetylene at a flowrate of 90 mL/min. For samples synthesised using acetylene at a flowrate of 120 mL/min, the crystallite size ranged from 3.1 to 4.4 nm. Raman spectroscopy confirmed the successful synthesis of MWCNTs; however, the intensity ratio (ID/IG) was found to be above 0.7 for a majority of the samples which confirmed the presence of impurities in the samples. SSA studies revealed that an inversely proportional relationship existed between the SSA and the synthesis temperature. vi HRTEM results for samples synthesised at 650°C and 700°C using ethylene at a flow rate of 90 mL/min (650°C-E90 and 700°C-E90) revealed that CNTs which were MWCNTs in nature were formed. As the synthesis temperature increased from 700°C to 800°C, the formation of what appeared to be non-tubular carbon and carbon nanofibers was observed. The average OD of the tubes ranged from 21 to 84 nm. At a higher ethylene flowrate (120 mL/min), the quality of CNTs seemed to deteriorate for synthesis temperatures above 700°C. The formation of non-tubular carbon-like nanofibers was observed at synthesis temperatures above 700°C. The average OD of the tubes ranged from 11 to 79 nm. XRD analysis of all samples synthesised using ethylene showed a similar pattern with the most intense peak being that of carbon and minor peaks being of iron. However, the depicted minor peaks were broad which suggested that the samples contained amorphous carbon. The calculated crystallite size ranged from 3.7 to 5.7 nm for samples synthesised using ethylene at a flowrate of 90 mL/min. For samples synthesised using ethylene at a flowrate of 120 mL/min, the crystallite size ranged from 3.6 to 6.5 nm. Raman spectroscopy confirmed the successful synthesis of MWCNTs. SSA studies revealed that the SSA decreased with an increase in the synthesis temperature. Furthermore, to evaluate the electrochemical performance of the synthesised material, electrodes of selected samples were fabricated. Commercial graphite electrodes were also fabricated to compare the performance with the samples synthesised in this study. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used for the electrochemical measurements. The CV tests were conducted at scan rates of 5 mV/s and 10 mV/s, An increase in the CV curve area was observed as the scan rate was increased. The calculated specific capacity of the samples compared well with that of the electrode fabricated with commercial graphite which reported an average of ~197 mAh/g after four cycles at a scan rate of 5 mV/s. The average specific capacity of the electrode fabricated with CNTs sample synthesised at 650°C using ethylene at a flowrate of 120 mL/min (650°C-E120) reported the highest value of 214 mAh/g after four cycles at a scan rate of 5 mV/s. Overall the variation between the samples of the EIS data was marginal. These EIS results also compared well with that of the electrode fabricated with commercial graphite. The findings of this work suggest that MWCNT electrodes have a good application potential and with doping, they may provide better electrochemical performance than graphite as a viable anode material for LIBs.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; CARBON NANOTUBES; LITHIUM-ION BATTERIES; ANODE; CHEMICAL VAPOR DEPOSITION; MULTIWALLED CARBON NANOTUBES; SDG-7: Affordable and clean energy